Peningkatan motivasi belajar siswa melalui pembelajaran berdiferensiasi dengan menggunakan media pembelajaran Google-Sites - Raharjo, Damai Rahmat; Sri Purnami , Agustina; Bukhori , Sarif (Piramida Akademi, 2024)
Although differentiated learning has been recognized as an effective approach to meeting diverse learning needs in the classroom, it is challenging to use learning media that are interesting and efficient for all students, as is found by teachers. This study explores the impact of using Google Sites learning media in increasing students' learning motivation through a differentiated approach in the classroom. This research was conducted as classroom action research involving the students of Class VII A in SMP Negeri 9 Yogyakarta. This study was undertaken within two cycles, in which every cycle had stages of planning, implementation, observation, and reflection. Data collection methods included observation, interview, and analysis of learning outcomes. The results showed a significant increase in students' learning motivation after implementing the differentiation approach by using Google sites as learning media. The practical implication of this study is that using technology in learning differentiation can increase students' participation and overall interest in learning.